Point of vue of primary school teachers toward the dimensional of national identity including in values of 2nd generation for third year primary. - benammar, achwak; boutera, belal (Journal of Social Sciences and Humanities, 2021)
Our study targets to reveal the viewpoint of teachers ,of the third year of primary education, towards the dimensions of identity included in the syllabus (Islamic Education - History - Civil Education) for the third year of primary education under the syllabuses of the second generation. The sample of our study was represented in all teachers of the third year of primary school for the school season 2018-2019, in the administrative district of taibet, the state of Ouargla ,and they were 44 teachers. For the success of our study, we followed the descriptive approach. The study is in light of the syllabus of the second generation . In the end , the study concluded that the teachers of the third year of elementary education were evaluating the syllabus of the social subjects under study in the light of the second- generation syllabus, due to the values they contain the national identity( especially the national, the historical and the Islamic dimensions), which contributes to the consolidation of the principles of the Islamic religion ,the glorification of the Arabic language and the support of the cultural heritages local and national, which characterizes Algerian society .